2019
DOI: 10.2196/12915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Technology-Based Peer-Support Intervention Program for Preventing Postnatal Depression (Part 2): Qualitative Study

Abstract: Background Social support is known to reduce risks of postnatal depression (PND) and improve maternal emotional well-being. However, the Asian cultural context is often neglected when appraising maternal needs and mothers’ preferences for social support. While many preventive efforts have experimented with technology, professionals, and paraprofessionals in providing social support to mothers in need, most studies determined the effectiveness of their interventions through quantitative measurements… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 66 publications
1
46
0
9
Order By: Relevance
“…Additionally, cultural differences largely influence the preferred types of support. Unlike individualistic Western culture, Asian culture is more collectivistic, and indirect support from other people giving companionship and attentiveness is preferred [60]. Therefore, cultural differences may account for the mothers' help seeking preference and behaviour in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, cultural differences largely influence the preferred types of support. Unlike individualistic Western culture, Asian culture is more collectivistic, and indirect support from other people giving companionship and attentiveness is preferred [60]. Therefore, cultural differences may account for the mothers' help seeking preference and behaviour in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, cultural differences may account for that mothers more preferred to seek helps from family members and peers in this study. It had been reported in other studies that peer support could help with generating sense of belongs, parenting confidence, self-esteem, and with preventing PPD [55,56]. This illustrated that Chinses cultural context should be considered when providing supports to mothers, and types of peer supports may be effective in solving mothers' problem.…”
Section: Discussionmentioning
confidence: 69%
“…Due to its profound influence, Chinese people may consider family conflicts and related mental health problems to be shameful and assume that they would lead to gossip and the communicate a negative impression of their entire family to others. This cultural context could be obvious in the other studies that Asian's higher value on family and social relationships, the mothers was regarded as a weaker sex and has more tendency to rely on others, especially on their family members and partner [55]. The results indicated that cultural factors, such as face -saving, should also be considered when conducting interventions in China.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, cultural differences largely in uence the preferred types of support. Unlike individualistic Western culture, Asian culture is more collectivistic, and indirect support from other people giving companionship and attentiveness is preferred [61]. Therefore, cultural differences may account for the mothers' help seeking preference and behaviour in this study.…”
Section: Discussionmentioning
confidence: 86%